Induction Strategies for Interferon-α2B Production in Periplasmic Space of Escherichia Coli - Azaman, Siti Nor Ani (2011)
Interferon-α2b (IFN-α2b) is a member of cytokine family with the ability to induce antiproliferative, antiviral, antineoplastic and immunomodulating activities. It is frequently used in the treatments of gastrointestinal tract diseases, various cancers and chronic hepatitis B. Due to its diagnostic and therapeutic potentials the production of IFN-α2b in large quantities is required to meet the demands from research, clinical and industrial applications. This study was carried out to enhance the production of recombinant IFN-α2b in the periplasmic space of E. coli using the recombinant E. coli Rosetta-gami 2(DE3) harboring the plasmid pET26b-IFN-α2b. In this study, different induction parameters (temperature, IPTG concentration, point of induction and post induction time) were analyzed and optimized during induction for optimal periplasmic IFN-α2b production. Further analysis was done on the effect of pH medium on IFN-α2b production in different fractions. Preliminary screening performed on four induction parameters shows that only three parameters (temperature, IPTG concentration and point of induction) improved the IFN-α2b production. These parameters were optimized individually by narrowing the working range as follows: temperature from 16°C to 30°C, IPTG lower than 2 mM, and induction point between early-log phase and mid-log phase on the growth curve of E. coli. A response surface methodology (RSM) based on a central composite design was used to optimize the induction parameters. The proposed induction strategy consisted of three optimized parameters: i) induction point at A600 of 4, ii) IPTG strength at 0.05 mM, and iii) induction temperature at 25°C. The strategy yielded 1.21 μg/mL of IFN-α2b, which represents 82% of the soluble IFN-α2b that was successfully transferred to the periplasmic space of E. coli after 18 h of induction. A study on the effect of pH on IFN-α2b production in different fractions reveals that the highest yield was obtained at pH 7 with a high buffering capacity (0.2 M). At this pH, a higher IFN-α2b production was obtained in the periplasmic fraction. Whereas, the amount of inclusion bodies formed was reduced. This was evident by the lack of aggregated materials in the cytoplasm of E. coli observed under the electron microscope. This study also proved that the suitable buffering capacity would maintain the pH of media during fermentation. Finally, when the optimized induction parameters with the appropriate media pH was applied, the total IFN-α2b obtained was 1.43 μg/mL, a 86.9-fold increase in productivity compared to the IFN-α2b produced under non-optimal condition (16.26ng/mL). Thus, proper optimization of fermentation conditions was proved useful to improve the production of periplasmic IFN-α2b in E. coli.